2014
DOI: 10.5370/jeet.2014.9.5.1501
|View full text |Cite
|
Sign up to set email alerts
|

A Techno-Economic Feasibility Analysis on LVDC Distribution System for Rural Electrification in South Korea

Abstract: -Low voltage direct current (LVDC) distribution system is a suitable techno-economic candidate which can create an innovative solution for distribution network development with respect to rural electrification. This research focuses on the use of LVDC distribution system to replace some of KEPCO's existing traditional medium voltage alternating current (MVAC) distribution network for rural electrification in South Korea. Considering the technical and economic risks and benefits involved in such project, a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The experience from the real rural ±750V LVDC test network as reported in [2] has concluded that LVDC is more efficient solution for rural AC networks when the feeder's lengths are over 1 km. LVDC distribution power systems have also been proposed to replace some of the Korea Electric Power Corporation (KEPCO) existing AC rural MV distribution networks (used for supplying light loads) in South Korea in order to save up to 5% of the total operating cost [16].…”
Section: Lvdc In Last Mile Power Distribution Networkmentioning
confidence: 99%
“…The experience from the real rural ±750V LVDC test network as reported in [2] has concluded that LVDC is more efficient solution for rural AC networks when the feeder's lengths are over 1 km. LVDC distribution power systems have also been proposed to replace some of the Korea Electric Power Corporation (KEPCO) existing AC rural MV distribution networks (used for supplying light loads) in South Korea in order to save up to 5% of the total operating cost [16].…”
Section: Lvdc In Last Mile Power Distribution Networkmentioning
confidence: 99%
“…However, in the case of DC distribution systems, the power conversion step can be omitted to enable a more efficient and economical operation, compared to the existing AC distribution system, when the DC distributed resources and DC consumers are connected [1]. Previous studies have confirmed the economics of the Direct Current (DC) distribution system [2]. In addition, the DC distribution system can effectively control voltage using the power conversion device instead of the transformer, and it can limit the fault current in case of an accident at the load side and prevent accidents from spreading to the main grid.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, many studies on AC/DC converters that connect with existing high-voltage AC systems are in development [2]. This paper focuses on the design, manufacturing, and demonstration of AC/DC power converters for converting high-voltage AC systems in a mountainous area, which come into frequent contact with trees, to an LVDC distribution system [3,4]. First of all, the capacity of the power converter is chosen by analyzing the load of the system, its switching elements, protection devices, and switching frequencies are chosen to ensure stable operation and high efficiency.…”
Section: Introductionmentioning
confidence: 99%